METAVERSE-BASED DIGITAL BUSINESS STRATEGY: ENTREPRENEUR AND CONSUMER PERSPECTIVES IN THE FASHION INDUSTRY - Khairun Nisa; Royanti Lusiana Lumbangaol; Nidya Banuari; Debora Tambunan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This study aims to explore how entrepreneurs and consumers in the fashion industry utilize and respond to the development of the metaverse as a digital business platform. The metaverse, as a virtual space that enables digital interactions in various forms, opens up new opportunities for entrepreneurs to expand their markets, create innovative consumer experiences, and present exclusive digital fashion products. On the other hand, consumers gain easier and more interactive access to fashion products, including the ability to try products virtually and gain access to exclusive items. This study uses qualitative methods with in-depth interviews and case study analysis to explore the perspectives of entrepreneurs and consumers. The results show that despite challenges related to technological infrastructure and consumer adoption, the metaverse is able to provide significant added value for both parties, both in terms of marketing, sales, and shopping experiences. Thus, the metaverse has the potential to become a key channel in the development of digital business strategies in the fashion industry, leading to a faster and more inclusive transformation in the global fashion ecosystem.